هندسة المعمار الفني في رواية نوار الملح لعبد الغني زهاني - عجرود, بريالة, هناء مليكة (Univercty of Eloued, 2020)
موضوع بحثنا جاء بعنوان هندسة المعمار الفني في الرواية تطبيقا على رواية نوار الملح لعبد الغني زهاني. ابتدأ بحثنا بمقدمة عرضنا فيها البناء الفني للرواية العربية ومدى علاقته في إحداث نقلة نوعية في الرواية العربية وتحقيق مستوى أفضل مروار بإبارز مستوى الرواية الجازئرية التي منها اخترنا رواية نوار الملح، مقدمين في التمهيد العلاقة بين الهندسة المعمارية والشكل الروائي وما أبرز العناصر المشكلة للبناء الفني وكيف يحقق لنا البناء الفني في انسجامه رواية متكاملة، فصلنا ذلك في فصلين كان الأول نظري بعنوان العناصر المشكلة للمعمار الفني الروائي، نظرنا فيه للعنوان والشخصيات، المكان، الزمان، اللغة والصورة الفنية. أما الفصل الثاني عنوناه بهندسة المعمار الفني في رواية نوار الملح فصلنا فيه في العناصر السابقة مطبقين ذلك على الرواية مستخلصين في النهاية جملة من النتائج. The subject of our research was titled Artistic Architecture in the novel, an application to Nawar al-Malh's novel by Abdul-Ghani Zhani. Our research began with an example in which we presented the artistic structure of the novel and the extent of its relationship in bringing about a qualitative leap in the novel and achieving a better level, passing by highlighting the level of the Algerian novel from which we chose the salt novel, presenting the relationship of architecture and the narrative form and what are the most prominent elements of artistic construction and how we started the artistic construction in its harmony An integrated novel, two chapters, the first was theoretical, starting with the constituent elements of artistic architecture. We looked at it, the characters, the place, the time, the language and the artistic image. As for the second chapter, entitled “Technical Architecture” in Nawar al-Malah’s novel, we separated the previous elements, applying that end of the novel, and extracting a set of results
Keywords: الجمالية الفنية ،هندسة المعمار الروائي البناء الفني; artistic construction, fictional architecture, artistic aesthetics